Best Papers from 2018 in the Environmental Science family of journals: great science with a global reach. Issue 4 (10th April 2019) - McNeill, Kristopher; Novak, Paige J.; Vikesland, Peter J.
Abstract : The Editors-in-Chief of the Environmental Science journals introduce the Best Papers of 2018.